Knoevenagel condensation using nitrogen-doped carbon catalysts. (November 2016) - Tanabe, Takehiro; Yamada, Yasuhiro; Kim, Jungpil; Koinuma, Michio; Kubo, Shingo; Shimano, Norimichi; Sato, Satoshi
Abstract: Nitrogen-doped carbon materials such as graphene and activated carbon have been studied as solid base catalysts. However, active sites of carbon catalysts have long been ambiguous because of the presence of various functional groups. This work clarified the dependence of positions of nitrogen atoms in aromatic hydrocarbons on catalytic activities of well-known Knoevenagel condensation of benzaldehyde with ethyl cyanoacetate to produce ethyl cyanocinnamate (ECC) as one of the examples for catalytic reactions. Catalytic activities of 30 kinds of aromatic hydrocarbons composed of one, two, and three aromatic rings with zero, one, two, and three nitrogen atoms were compared. Phenazine with zigzag edges and pyridinium ion with quaternary nitrogen showed low catalytic activities. On the other hand, 1, 10-phenanthroline with armchair edges showed a high ECC selectivity of 99.3% and a high ECC yield of 59.0%. Among various aromatic hydrocarbons carbonized on silica, 1, 10-phenanthroline carbonized at 923 K exhibited the highest ECC selectivity of 89.5% and the highest ECC yield of 10.2% because of the highest percentage of 1, 10-phenanthroline-like N after carbonization. We believe that this work can serve as a perfect example to examine the performance of carbon catalysts at a molecular level in the future. Graphical abstract: